Rekonstruksi Hukum Adat Terhadap Pelanggaran Protokol Kesehatan Selama Pandemi Covid-19 di Desa Adat Kota Tabanan - Diah Gayatri Sudibya; Dessy Lina Oktaviani Suendra; Kade Richa Mulyawati (Fakultas Hukum, Universitas Warmadewa, 2021)
The higher the number of people affected by COVID-19, the government continues to aggressively issue regulations to suppress the growth of new cases and minimize new clusters of the spread of COVID-19. The Tabanan City Traditional Village, which has been listed twice as being in the red zone for the spread of Covid-19, is responding to the increasingly rampant Covid-19 pandemic problem by forming a perarem or customary rules that apply to the local Traditional Village, namely the Tabanan City Customary Regulation Number 5 of 2020 on the Regulation of Prevention and Control of Gering Agung Covid-19. This Perarem was ratified on July 19, 2020 and has been gradually socialized to the traditional banjars. The purpose of the formation of this regulation itself is to break the chain of the spread of Covid-19 and increase the discipline of the village community because this regulation also includes fines. As for the problem that will be studied, how are the legal arrangements regarding violations of health protocols during the Covid-19 pandemic in the traditional village of Tabanan city? and how is the ideal reconstruction of customary law in overcoming violations of health protocols during the Covid-19 pandemic in the traditional village of Tabanan city?. The method used in this research is the empirical legal method and is studied with a statutory approach. The results of this study are the traditional village of Tabanan City already has the Pararem of the Traditional Village of Tabanan City Number 5 of 2020 which includes fine sanctions for violators of the health protocol, only that there are still many people who do not comply with these regulations. To overcome this, it is necessary to reconstruct norms so that there are no gaps that can be exploited by health protocol violators.